(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Arjuna got divine being as a teacher, guide, counselor, and leader when he was depressed and confused. Meanwhile, he was not ready to fight against evil deeds and was hopeless due to nepotism, favoritism, and anxiety of losing own dearly family members after the battle that he was going to take part. So he did surrender like poor and unskilled warier despite having extra level of divine power within him. In the same way, the Nepalese educators have also been facing multiple challenges, confusions, depressions, and divergences not because of lack of knowledge and skills but because of proper guidance, required professional input, and the leadership like Krishna. Therefore, this literature review study aims to explore the role of Bhagvad Gita wisdom for the transformation of Nepalese educators for their personal, professional, social, and spiritual betterment through the framework of content analysis method with theoretical base spiritual intelligence theory and transformative learning theory. Furthermore, this study delves into how the Karma Yoga, Jnanvijnan Yoga, and Dhyan Yoga can lead the Nepalese educators to the liberation acquainting and involving them in selfless action, ultimate truth and renunciation of desires to dedicate their actions in the name of God and be role model for the students and society.